An empirical analysis of the impact of crude oil spot and futures prices volatility on the development of African equity markets - Ibrahim A. O. Bakare; Mahmud O. Quadry; Mohammad Abdul-Matin Chowdhury (Economic and Environmental Studies (E&ES), 2018)
This study focused on the impact of crude oil, crude palm oil spot and futures of prices on African equity markets. It draws on daily data from January 2000 till July 2013, obtained from Bloomberg. The study employed Vector Error Correction (VEC). Findings from the econometric analysis show that there is relativity in the speed of adjustment among such countries' equity market index as Mauritius, whose economic backbone is tourism, which responded faster compared with other ' equity markets. Kenya's equity market index responded positively relative to those of Morocco and Nigeria, while South Africa's equity market responded slowly, unlike other equity markets. The implication of Morocco and Nigeria's equity markets adjusting slowly to the shock from crude oil market crisis was due to a high dependence of the governments of both countries on crude oil revenues in financing their economic activities. The study shows the existence of a long-term relation between crude oil, crude palm oil spot and futures prices on equity markets. The VECM Granger causality test was applied to examine the association and impact among these variables. The results indicate that crude oil spot and futures price granger influence the equity markets of Mauritius, Kenya and Morocco, while futures prices of crude oil granger impact Nigeria's and South Africa's equity markets.
Keywords: O13; Q48; N27; L29; 330; crude oil; volatility; equity markets; revenue